Strategi Keluarga Burhanudin Mohamad Diah Dalam Memperkuat Solidaritas Keluarga Di Negara Sosialis, 1959-1962 - Ayu Wulandari (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
This article discusses the strategy of Burhanuddin Mohamad Diah's family as an ambassador's family in strengthening family solidarity when assigned to two socialist countries, namely Czechoslovakia and Hungary from 1959 to 1962. This article analyzes why family solidarity became so important for their lives in diplomatic posts, the channels and media used to strengthen this solidarity, and the role of women in it. This article was carried out using historical research methods which utilize various primary sources, ranging from ego documents, contemporary publications, oral history, to a number of official archives. This article reveals that family solidarity at diplomatic posts was part of the comfort conditions for the B. M. Diah family. This is due to two factors, namely historical factors and family psychological factors. To build and strengthen family solidarity, the B. M. Diah’s family used a number of channels, spaces, and media, including the family's domestic space, arts, sports, and tourism. This article also reveals that the presence of family solidarity issues has encouraged the emergence of women's agency and activism in the B. M. Diah family. To be precise, B. M. Diah’s wife, Herawati Diah, was present as a driving force, leader, and decision maker in the family in order to strengthen their internal solidarity.